The Representation of Gender and Women's Cultural Differences in Bothayna Al-Essa's "Dar Khawla" - Anas A. Alhumam (Journal of Arts, Literature, Humanities and Social Sciences, 2026)
This paper examines Bothayna Al-Essa’s novel Dar Khawla to analyze how gender and women’s cultural differences are represented in Al-Essa’s work. Qualitative study design was employed to investigate these dimensions through textual and thematic analysis with respect to various cultural and feminist theoretical frameworks. As Dar Khawla is centralized on the themes of gender identity, postcolonial critique and cultural identity, it explored the role of language and identity construction within female characters penned by Al-Essa. It focuses on the interconnection of cultural transformation with relation to Butler’s gender performativity theory and Bhabha’s cultural identity. It connects cultural identity to examine Al-Essa’s portrayal of Kuwaiti national identity, highlighting her engagement with cultural diversity. Gender performativity and female identity construction highlighted the themes of freedom and looking at cultural expectations as a means of liberation instead of limitations. It explores the interplay between narrative and lyrical elements in feminist writing, offering rich theoretical insights. The study employs Susan Stanford Friedman’s ideas on narrative and poetic interaction to demonstrate how feminist literature reconfigures literary structures. Al-Essa’s work combines poetic and narrative techniques, amplifying women’s voices in resistance and conveying their experiences as a marginalized group within dominant male narratives. The analysis reveals Al-Essa’s intertextuality in amplifying female voices while addressing empowerment, societal reform, and intellectual inquiry. Her advocacy for the Arabic language and cultural heritage highlights the importance of preserving identity amid globalization, while her engagement with Western culture reflects a blending of traditional values and modern influences.